Does good governance contribute to pro-poor growth?: a review of the evidence from cross-country studies - Resnick, Danielle; Birner, Regina (International Food Policy Research Institute, 2006)
Even though both “good governance” and “pro-poor growth” have become important concepts in development thinking and practice, studies that assess to which extent and how good governance contributes to pro-poor growth are still relatively scarce. After reviewing the two concepts, this paper develops a conceptual framework that specifies the linkages between different aspects of governance and pro-poor growth. Using this framework, the paper reviews a range of quantitative cross-country studies that include measures of governance as independent variables and focuses on the dependent variable in at least two of the three dimensions of pro-poor growth: poverty, inequality, and growth. The review shows that governance indicators that capture a sound decision-making environment for investment and policy implementation, such as political stability and rule of law, are associated with growth but provide mixed results in regard to poverty reduction. On the other hand, governance indicators that refer to transparent political systems, such as civil liberties and political freedom, tend to be conducive for poverty reduction, but the evidence is rather mixed, and the relationship of these variables with growth remains unclear. The paper discusses the methodological challenges inherent in this literature and suggests areas for future research.